Creativity and skills formation features creative thinking in preschool children through literary creation.: Creativity and skills formation features creative thinking in preschool children through literary creation. - Anorboev, Akmal (Maktabgacha taʼlim jurnali, 2021)
creative, thinking, intellectu creative, thinking, intellectual, abilities, experience, ideas, development, pedagogical, personality. al, abilities, experience, ideas, development, pedagogical, personality.